The forest structure of Irawan, Palawan - Banez, George V. (Animo Repository, 1991)
The structure of one hectare of Irawan, Palawan is studied using the strip transect method. Five hundred eighty-eight (588) trees with DBH 10 centimeters or more were found in the plot. These belonged to 192 species, 70 genera and 35 families. Based on the importance value, the two co-dominant species were Dysoxylum rubrum (Lambuanao) and Canarium asperum (Sahing). Based on the profile diagram, the trees in the plot were stratified in 3 layers: Layer A trees were 25-50 meters in height Layer B trees with the height of 12-20 meters and Layer C trees of not more than 10 meters in height. The computed species diversity index was 9.2 and the total basal area cover was 46 m2. The study indicates that the Irawan forest is stable, diverse and a typical example of a primary tropical rain forest making its conservation imperative.